2022
DOI: 10.3390/ijms23137424
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Their Impact on Protein Modification in Human Cells

Abstract: Reactive oxygen species (ROS) represent a group of molecules with a signaling role that are involved in regulating human cell proliferation and differentiation. Increased ROS concentrations are often associated with the local nonspecific oxidation of biological macromolecules, especially proteins and lipids. Free radicals, in general, may randomly damage protein molecules through the formation of protein-centered radicals as intermediates that, in turn, decay into several end oxidation products. Malondialdehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…ALEs-HSA may also be involved in increasing the production of autoantibodies in some autoimmune disorders, such as systemic lupus erythematosus and arthritis [ 61 , 62 ]. It is well known that aldehydes are capable of binding to proteins and forming fluorescent compounds with a maximum emission wavelength of 440–480 nm [ 63 , 64 ]. Time-resolved fluorescence spectroscopy has been used to study the interaction between MDA and HSA (ALEs-HSA formation).…”
Section: Introductionmentioning
confidence: 99%
“…ALEs-HSA may also be involved in increasing the production of autoantibodies in some autoimmune disorders, such as systemic lupus erythematosus and arthritis [ 61 , 62 ]. It is well known that aldehydes are capable of binding to proteins and forming fluorescent compounds with a maximum emission wavelength of 440–480 nm [ 63 , 64 ]. Time-resolved fluorescence spectroscopy has been used to study the interaction between MDA and HSA (ALEs-HSA formation).…”
Section: Introductionmentioning
confidence: 99%
“…† Numerous studies have reported the antioxidant properties of avonols, a subclass of avonoids. 45,46 The present study conrms quercetin's free radical scavenging ability through EPR spin trapping spectroscopy, and the results are on par with the reduction of NOX-4 expression in samples treated with quercetin prior to stimulation. Thus, quercetin inhibits oxidative stress by reducing the expression of NOX4.…”
Section: Discussionmentioning
confidence: 59%